2008
DOI: 10.1007/s10964-008-9317-4
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Change from Adolescence to Emerging Adulthood: Adolescence-limited vs. Life-course-persistent Profound Ego Development Arrests

Abstract: Participants (n = 36) with consistent Pre-conformist ego development levels during multiple adolescent assessments were studied to determine whether and how their ego levels had changed at age 25. Those (n = 12) whose ego levels remained at the Pre-conformist level were assigned to a life-course-persistent profound ego development arrest trajectory group; those (n = 24) whose ego levels reached the Conformist or Post-conformist level at age 25 were assigned to an adolescence-limited profound ego development ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In adolescence, these youth were between Level 3, Self-Protective, and Level 4, Conformist, and they remained near self-protective as they transitioned to emerging adulthood. Although the frequency of this group was quite small in the present sample, it is a theoretically important group that has been previously identified and examined in detail by Billings et al, 2008. Future research with larger samples is necessary to better understand the factors that inhibit personality development in this group.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In adolescence, these youth were between Level 3, Self-Protective, and Level 4, Conformist, and they remained near self-protective as they transitioned to emerging adulthood. Although the frequency of this group was quite small in the present sample, it is a theoretically important group that has been previously identified and examined in detail by Billings et al, 2008. Future research with larger samples is necessary to better understand the factors that inhibit personality development in this group.…”
Section: Discussionmentioning
confidence: 77%
“…There has been some research on individual trajectories of ego development. Hauser and colleagues (Billings, Hauser, & Allen, 2008; Hauser et al, 1991; Henninghausen, Hauser, Billings, Schultz, & Allen, 2004) have described six theoretical trajectory types for how individuals change in ego development over time, three of which represent stability (stable high, moderate, and low) and three represent change (increase, decrease, and fluctuating). Empirically, they have found evidence for all of the trajectory classes except for decreasing, with the stable moderate trajectory being the most common among healthy adolescents.…”
Section: Individual Change In Ego Developmentmentioning
confidence: 99%
“…Emerging adulthood is now largely conceptualized and researched as distinct from both adolescence and later adulthood (Arnett, 2007;Billings, Hauser, & Allen, 2008;Steger, Oishi, & Kashdan, 2009; for a different perspective, see also Bynner, 2005). Emerging adults can be described as experiencing aspects of adulthood and adolescence simultaneously.…”
mentioning
confidence: 99%
“…Higher ego development was also negatively correlated with defensive coping techniques, including regression, isolation, and projection. In other studies (Billings, Hauser, & Allen, 2008;Hennighausen, Hauser, Billings, Schultz, & Allen, 2004), individuals who displayed higher levels of ego development through early adulthood were rated as less hostile, more socially adept, and more able to engage in collaborative conflict resolution than individuals who remained arrested in early stages of ego development. Further, research with non-substance-abusing samples has shown a curvilinear relationship between ego development and internalizing disorders, including anxiety and depression (Noam, Young, & Jilnina, 2006).…”
Section: Ego Development and Psychosocial Functioning In Nonpsychiatr...mentioning
confidence: 76%